Optimal Sizing of Renewable Energy-Based Charging Infrastructure for Electric Vehicles - Ahmed O.M.A.; Wali S.B.; Hannanl M.A.; Ker P.J.; Manser M.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Costs; Electric power transmission networks; Electric vehicles; Gas emissions; Greenhouse gases; Secondary batteries; Vehicle-to-grid; Battery energy storage systems; Charging station; Cost of energies; Electric vehicle charging; Electric vehicle charging station; Energy-based; Greenhouse gas emissions; Hybrid energy storage systems; Net present cost; Renewable energies; Renewable energy resources